2016
DOI: 10.4049/jimmunol.1600771
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Syk-Dependent T Cell Signaling Response to an Altered Peptide

Abstract: Rheumatoid Arthritis (RA) is an autoimmune disorder characterized by T cell dysregulation. We have shown that an altered peptide ligand (A9) activates T cells to utilize an alternate signaling pathway which is dependent upon FcRγ and Syk, resulting in downregulation of inflammation. In the experiments described herein we have attempted to determine the molecular basis of this paradox. Three major SFKs found in T cells (Lck, Fyn, and Lyn) were tested for activation following stimulation by A9/I-Aq. Unexpectedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The exact mechanism for A12 immunosuppression has not been definitively established but there is substantial circumstantial evidence that it exerts its effects through activation of an alternative signaling pathway. We have previously shown that an altered peptide ligand (A9) which is restricted by the murine I-A q -can activate T cells to utilize an FCRγ-dependent alternative signaling pathway (810). In the present experiments we address two important questions.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism for A12 immunosuppression has not been definitively established but there is substantial circumstantial evidence that it exerts its effects through activation of an alternative signaling pathway. We have previously shown that an altered peptide ligand (A9) which is restricted by the murine I-A q -can activate T cells to utilize an FCRγ-dependent alternative signaling pathway (810). In the present experiments we address two important questions.…”
Section: Introductionmentioning
confidence: 99%